(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Studies on the diversity and density of macroalga have been carried out in Ambalau island waters, south Buru district since 2010. The purposes of this study were to determine the diversity, density, frequency, and the dominance of macroalga in the coastal waters of the Ambalau island. Data collection with squares transect line method were conducted in October-November 2009. The results showed that the coastal areas of Masawoy showed the highest values in diversity, density, frequency, and the dominance of macroalga in the study area with 33 species from 20 genera consisting of 14 species of green alga, 10 species of red alga, and 9 species of brown alga. Caulerpa, Halimeda, Gracilaria, Acanthophora, Sargassum, and Padina were the most dominance in the region. The highest diversity, density, frequency, and dominance of macroalga on the Masawoy coastal waters were due to its habitat conditions in relatively good condition consisting of dead coral rubble, sand, coral live with seagrass vegetation dominated by Thalasia hemprizii and Enhalus acuroides. Meanwhile, habitat conditions at other locations have suffered a severe damage and dominated by dead coral. Environmental conditions in the study region were within the limits of decent support for the growth of macro alga. Keywords: macroalga, biodiversity, density, frequency, dominance, Ambalau